Fully Digital Phased Array Harmonic Radar for Detecting Concealed Electronic Devices - Wonryeol Lee; Taeyong Jeong; Daju Lee; Kyusik Woo; Kang-Yoon Lee; Chang-Ryul Yun; Chulhun Seo; Juntaek Oh; Keum Cheol Hwang; Sun K. Hong (IEEE Journal of Microwaves)
This paper presents the design and performance evaluation of a fully integrated digital phased array-based nonlinear radar system. The proposed system employs a bi-static structure, where the transmitter and receiver are physically separated. The transmitter operates at 3–3.2 GHz, while the receiver is designed to capture the second harmonic responses at 6–6.4 GHz. The system consists of 64 channels for both transmission and reception, enabling electronic beam steering through phase shift control. To enhance the beamforming accuracy, a novel transmitter calibration method utilizing an oscilloscope instead of a network analyzer was implemented. The method simplifies synchronization requirements while maintaining precise phase alignment. Performance evaluation of the radar system was conducted through experimental validation in both free-space and concealed conditions, using arbitrary commercial electronic devices as targets. The experimental validation results demonstrated an average range error of 32.3 cm with a range resolution of 37.5 cm. Additionally, multi-target detection was performed using beamforming techniques. In free-space conditions, the radar achieved accurate target localization with angular errors below 1°. In concealed conditions, nonlinear reflections introduced minor localization errors due to clutter. Despite these challenges, the system successfully detected multiple targets by employing a clustering method. To the best of our knowledge, the system presented here is the first demonstration of a fully integrated digital phased array-based nonlinear radar in the open literature.